Influence of the soil microbial populations on population density of Beauveria bassiana under the effect of insecticides - Soares, Flávia Barbosa; Monteiro, Antonio Carlos; Barbosa, José Carlos; Mochi, Dinalva Alves (Científica, 2017)
This study aimed to assess whether the populations of bacteria, fungi and actinomycetes from soil influences the effect of insecticides, applied in different time points, on the survival of Beauveria bassiana. Insecticides containing the active ingredients abamectin, thiamethoxam, carbofuran and chlorpyriphos were used at the doses recommended by the manufacturer. Initially, the effect on B. bassiana was evaluated in a culture medium containing the insecticides. Next, the insecticides were added to the soil 1 hour before, 1 hour after, and 48 hours after inoculation with the fungus. The density of the native populations of bacteria, fungi and actinomycetes, and the population of B. bassiana were assessed. Chlorpyriphos was classified as toxic to the fungus in culture medium and inhibited survival of the entomopathogen in the soil. The other insecticides tested did not affect the fungus. The soil microbial populations have little influence on the effect of insecticides for B. bassiana. The bacterial population was the only factor that influenced the toxicity of chlorpyriphos to B. bassiana. The actinomycetes negatively influenced the survival of the entomopathogen, and the fungi population had only a small inhibitory effect on the population density of B. bassiana. The time point of application does not influence the effect of insecticides on the fungus in the soil.